Initial coefficients and Fekete-Szego inequality for a subclass of analytic functions associated with q-Salagean differential operator - Lai Kha Hui; Aini Janteng; Jaludin Janteng (Hikari, Ltd, 2025)
In this paper, we introduce a new subclass of analytic functions associated with the q-Sălăgean differential operator. It determines the initial coefficients a_2 and a_3 and establishes the upper bound for the Fekete-Szegö inequality |a_3-〖δa〗_2^2 | within this subclass.